The epidemiology and burden of atherosclerotic cardiovascular disease in China from 1990 to 2021: findings from the global burden of disease 2021 - Hou, Xin-Zheng; Wu, Qian; Yang, Ying-Tian; Ye, Xue-Jiao; Lv, Qian-Yu; Yang, Chen-Yan; Huang, Ming-Yu; Wang, Shi-Han (Frontiers in Public Health, 2025)
BackgroundAtherosclerotic cardiovascular disease (ASCVD) significantly threatens the health of the Chinese population. Understanding its epidemiological burden is vital for targeted interventions.MethodsUsing Global Burden of Diseases (GBD) 2021 data, we assessed Disability-Adjusted Life Years (DALYs), incidence, prevalence, and mortality of ischemic heart disease (IHD), stroke, and lower extremity peripheral artery disease (PAD) in China in 2021. Joinpoint regression analyzed trends from 1990 to 2021, and risk factor contributions to the disease burden were evaluated.FindingsIn 2021, age-standardized rates (ASRs) per 100,000 population for IHD (DALYs, incidence, prevalence, mortality) were 1856.5 (1548.7, 2159.8), 365.7 (293.3, 440.1), 3042.3 (2601.7, 3629.9), and 110.9 (92.4, 128.6), respectively, with males bearing a higher burden. For stroke, ASRs were 2648 (2253.4, 3076.9), 204.8 (181, 231.5), 1301.4 (1200.6, 1405.7), and 138 (116.7, 160.3), also higher in males. Lower extremity PAD showed ASRs of 8.4 (4.9, 14.3), 112.7 (97.8, 130.7), 1331.1 (1147.5, 1544.2), and 0.1 (0.1, 0.2), with a higher burden in females. Metabolic risks had the largest population-attributable fraction.ConclusionAs of 2021, the epidemiological burden of IHD, stroke, and PAD in China remains substantial, with notable gender disparities. Metabolic risks significantly contribute to this burden.